Hypoxia-inducible factor 2-alpha-dependent induction of amphiregulin dampens myocardial ischemia-reperfusion injury - Michael Koeppen (Nature Portfolio, 2018)
Myocardial ischemia–reperfusion injury stabilizes the hypoxia-inducible factor HIF2-alpha. Here, the authors show that HIF2-alpha protects the heart from injury via induction of the epidermal growth factor amphiregulin, and that amphiregulin administration is cardioprotective in mice.